MAGIC MUSHROOM AND ITS EFFECTIVENESS - C. MERIBHA CHRISTY (International Journal of Pharma and Bio Sciences, 2016)
Mushrooms are probably the best known fungi and usually found springing up on dead wood after cool, wet weather; the mushroom is a common sight. Psilocybin mushrooms, also known as psychedelic mushrooms, are mushrooms that contain the psychedelic compounds psilocybin and psilocin. It is used mainly as an antigen and recreational drug whose effects can include euphoria, altered thinking processes, closed and open-eye visuals, synaesthesia, an altered sense of time and spiritual experiences. Magic mushrooms are one of the most widely used recreational psychotropic drugs because they can be found in the wild or grown fairly easily and inexpensively.